PERAN PEMERINTAH DALAM PENYELENGGARAAN BIMBINGAN TEKNIS KPPS PADA PEMILU TAHUN 2024 DI KOTA CIMAHI - Yovinus; Rira Nuradhawati; Imanda Setyawan (Mimbar Administrasi Mandiri, 2024)
The role of the Cimahi City Regional Government is very important in organizing Technical guidance and all stages of the 2024 General Election in the Cimahi City General Election Commissions working area. Apart from budgeting, regional governments are also responsible for ensuring that elections in their working areas run smoothly. One important part of the preparation for holding elections is the existence of technical guidance activities for all Voting Organizing Group members who work in Cimahi City. This is to ensure that all election organizing officers are ready to carry out their roles and functions. The purpose of this research is to understand and find out about the implementation of Technical Guidance for Voting Organizing Group Members in Cimahi City. The method used in this research is a qualitative research method with an observation approach. The observation approach in research is a scientific method in research in an effort to record and directly observe the phenomena that occur in Cimahi City during preparations for the 2024 General Election in Cimahi City. The research results show that the Cimahi City Government has made maximum efforts to ensure that the 2024 General Election runs smoothly. One of the efforts to ensure that the elections run smoothly is through the implementation of technical guidance for Voting Organizing Group members as the spearhead in organizing the 2024 elections. In developing knowledge, this research can contribute to adding scientific treasures and references within the scope of Government or Public Administration Science related to the implementation Election.